ABOUT THE NATURE OF METEOR FLARES - Smirnov, V. A. (Одеські астрономічні публікації, 2016)
Whereas at development of the meteoric phenomenon there are processes in different temporary scales (more slow processes heat conductivity, mechanical rotation, destruction) and considerably faster (fluctuations of brightness of radiating plasma is like gas-dynamical laser), the observable flares of meteors differ in nature, and in appearance caused by character of radiation. Continuing development of the meteoric phenomena in the Earth’s atmosphere has been described by Astapovich I.S. (Astapovich I.S. 1958). The classification of meteor flashes which depends on the physical nature of the phenomenon is given below and the formulas of a physical theory representing these processes while moving the meteor are presented here.